Vom Leben zur Bedeutung philosophische Studien zum Verhältnis von Gefühl, Bewusstsein und Sprache - Engelen, Eva-Maria 1963- (De Gruyter, 2014)
Howcan an ego-less sense of the self be created? How is the step to self-awareness accomplished? And how does an emotional response become a value judgment? The author examines such transitional moments between various manifestations of mind. She reflects upon the role of language as well as the idea of intentionality as an element in the theory of emotions, the theory of linguistic meaning, and the philosophy of mind
Keywords: Philosophie; Intentionality (Philosophy); Self-consciousness (Awareness); PHILOSOPHY / Movements / Humanism; Philosophy of mind; Mentalismus; Geist; Prozessphilosophie